2023
DOI: 10.2147/jir.s401430
|View full text |Cite
|
Sign up to set email alerts
|

GBP5 Expression Predicted Prognosis of Immune Checkpoint Inhibitors in Small Cell Lung Cancer and Correlated with Tumor Immune Microenvironment

Qin Tong,
Deyu Li,
Yan Yin
et al.

Abstract: Background The discovery and development of immune checkpoint inhibitors (ICIs) has significantly enhanced the arsenal of immunotherapy treatments available for cancer patients. The identification of biomarkers that are indicative of an individual’s sensitivity to treatment with ICIs is useful for screening SCLC patients prior to commencement of any ICIs based immunotherapy. However, the relationship between GBP5 and the prognosis of SCLC immunotherapy is still unclear and requires further study. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…As we mentioned, T cells in cancers is associated with better outcomes of tumor patients [28]. Previous studies have found that lung cancer patients with high GBP5 respond better to immunotherapy and have a better prognosis [29], and we rstly found that GBP5 may be bene cial for patients in SKCM. In addition, the PRDM1, PIM2 and IL27RA have also been found to affect the prognosis and development of tumors, such as hematological malignancies and hepatocellular carcinoma [30][31][32], and their roles in SKCM have been reported for the rst time.…”
Section: Discussionmentioning
confidence: 58%
“…As we mentioned, T cells in cancers is associated with better outcomes of tumor patients [28]. Previous studies have found that lung cancer patients with high GBP5 respond better to immunotherapy and have a better prognosis [29], and we rstly found that GBP5 may be bene cial for patients in SKCM. In addition, the PRDM1, PIM2 and IL27RA have also been found to affect the prognosis and development of tumors, such as hematological malignancies and hepatocellular carcinoma [30][31][32], and their roles in SKCM have been reported for the rst time.…”
Section: Discussionmentioning
confidence: 58%
“…Memory B cell, Effector memory CD4 T cell, Central memory CD4 T cell and Activated dendritic cell were associated with more than two key genes ( p < 0.001). HOOK1 is strongly associated with M2 macrophages in endometriosis (Wang et al, 2023 ), and GBP5 is associated with a high infiltration of B-cells, CD4+ T-cells, CD8+ T-cells, and NK-cells in small cell lung cancer (Tong et al, 2023 ). These high correlations suggest an important role for these genes in immune regulation and inflammation.…”
Section: Discussionmentioning
confidence: 99%